¿Cuál es la idea que nos han dejado Juan Santos Atahualpa y Túpac Amaru? - Enrique Casanto; Vicente Romero (Les Cahiers ALHIM)
Enrique Casanto managed to make university studies despite many problems, common to the Asháninka people. In this interview he relates his personal path and his work as a researcher. He also tells about his experience as a Regional Councillor and the evolution of the organization of the central jungle’s people.